2020
DOI: 10.1002/jor.24617
|View full text |Cite
|
Sign up to set email alerts
|

Detecting total hip replacement prosthesis design on plain radiographs using deep convolutional neural network

Abstract: Identifying the design of a failed implant is a key step in the preoperative planning of revision total joint arthroplasty. Manual identification of the implant design from radiographic images is time‐consuming and prone to error. Failure to identify the implant design preoperatively can lead to increased operating room time, more complex surgery, increased blood loss, increased bone loss, increased recovery time, and overall increased healthcare costs. In this study, we present a novel, fully automatic and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 23 publications
4
109
0
Order By: Relevance
“…Other studies have applied DL methods on plain film radiographs for various orthopedic applications [7][8][9][10][11][12][13][14][15][16] . However, to the best of our knowledge, our pilot study identifying three types of THR femoral implant designs 18 , and this study identifying nine types of THR femoral implant designs are the first applications of DL method to automatically detect THR femoral implant designs. We demonstrated that the CNN generally achieved on-par accuracy with the surgeons in identifying these THR implant designs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have applied DL methods on plain film radiographs for various orthopedic applications [7][8][9][10][11][12][13][14][15][16] . However, to the best of our knowledge, our pilot study identifying three types of THR femoral implant designs 18 , and this study identifying nine types of THR femoral implant designs are the first applications of DL method to automatically detect THR femoral implant designs. We demonstrated that the CNN generally achieved on-par accuracy with the surgeons in identifying these THR implant designs.…”
Section: Discussionmentioning
confidence: 99%
“…Online data augmentation created realistic new x-rays, preserving the same constant design of each THR implant, while compensating for intrinsic x-rays variations. We successfully followed this online data augmentation method in our previous work 18 with smaller range (horizontal flip, rotation between 0° and 25°, width and height shift between 0% and 15%, shearing between 0% and 10%, and magnification between 0% and 15%), and less number of epochs (350 epochs). We had to increase both the data augmentation range and number of epochs in this study due to the more complex classification task compared to our previous study (nine THR implant designs in this study vs. three THR implant designs in our previous study).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Machine learning itself can be further divided into more classical algorithms (e.g., support vector machine, decision tree, and neutral network) to extract knowledge from tabulated data sets, [2][3][4][5] and more recently developed ''deep learning'' algorithms (e.g., convolutional neural network [CNN]) to extract knowledge from imaging data sets. 6 Since orthopedic diagnosis and prognosis rely heavily on manual interpretation of medical images (X-ray, computed tomography scans, and magnetic resonance imaging), the application of AI in orthopedics has mainly focused on implementation of deep learning on these images. Deep learning can help radiologists and orthopedic surgeons with automatic interpretation of medical images that can potentially improve the diagnostic accuracy and speed, flag the most critical and urgent patients for immediate attention, reduce the amount of human error due to fatigue and/or inexperience, reduce the strain on medical professionals by reducing their workload, and, in general, improve orthopedic care.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning has been successfully used in different orthopedic applications such as fracture detection, [7][8][9][10] bone tumor diagnosis, 11 detecting hip implant mechanical loosening, 6 and grading osteoarthritis. 12,13 The implementation of deep learning in orthopedics is not without challenges and limitations.…”
Section: Introductionmentioning
confidence: 99%